ChemInform Abstract: Efficient Ullmann C—N Coupling Catalyzed by a Recoverable Oligose‐Supported Copper Complex. Issue 46 (October 2016) - Ge, Xin; Chen, Xinzhi; Qian, Chao; Zhou, Shaodong
Abstract: A β‐cyclodextrin supported copper complex is successfully employed as catalyst for the coupling reaction of various N‐nucleophiles and aryl halides.